A responsabilidade do setor bancário na concessão do crédito - Pereira, Adriana Cristina (2014)
In search of the upturn in the economy, six years ago the State and the financial institutions have encouraged the granting of credit to consumers from all economic classes, eager to enter the consumer Market they have been induced by the loan offers, credit cards and overdrafts. Thus, household debts have grown steadily and, consequently, default rate has increased. In this sense, the present work aims to determine the liability of financial institutions regarding the default because they offer easy credit in an unrestricted manner, stimulating the consumer to consume increasingly to take on huge debts which often become unpayable. The choice of this theme is based on the importance of itself, given the risk of unrestricted credit and rising consumer debt, beyond the actuality of the topic in recent years. The growth of the supply of abusive credit, lack of risk analysis by financial institutions, the lack of information with regard to contractual terms ( interest rate , loan amount ) , led consumers to consume and borrow even more . So based on these dictates and on the guiding principles of the Federal Constitution, we must highlight the responsibility of the banking sector in this matter, since the consumer cannot be solely responsible for taking the credit and also for the default rate of this obligation.